Choledochal Cyst and Malignancy: A Plea for Lifelong Follow-Up - Madadi-Sanjani, Omid; Wirth, Thomas C.; Kuebler, Joachim F.; Petersen, Claus; Ure, Benno M. (European Journal of Pediatric Surgery, 2019)
Previous research has confirmed that patients with choledochal cyst have an elevated risk of cholangiocarcinoma and gallbladder carcinoma. Current data suggest a risk of malignancy of 6 to 30% in adults with choledochal cyst. Malignancy has also occasionally been identified in children and adolescents. Multiple factors, including the age of the patient, cyst type, histological findings, and localization, have an impact on the prognosis. Information on long-term outcomes after cyst excision is limited. However, recent data suggest a lifelong elevated risk of up to 4% of cancer development following operation. This paper presents a review of the literature on cancer in patients with choledochal cyst before and after excision. A postoperative follow-up concept that consists of annual controls of CA19–9 and abdominal ultrasound is introduced.
Keywords: choledochal cyst; cholangiocarcinoma; gallbladder carcinoma; cyst excision; follow-up